Breast milk and Bottle Milk in relation with gastroenteritis - Rumondang Rumondang; Suharyono Suharyono; Aswitha Budiarso; Mugijo K. Utomo; Adnan S. Wiharta (Paediatrica Indonesiana, 1979)
A study on 1043 children aged 3 days to 2 years hospitalized in the Department of Child Health, from 1 January to 31 December 1976, was made fo find out the relation between breast milk and bottle milk with gastroenteritis, especially concerning bacterial, fungal infection and fat malabsorption.